"Why me? I don't fit the mould … I am a freak of nature": a qualitative study of women's experience of gout. Issue 1 (December 2015) - Richardson, Jane; Liddle, Jennifer; Mallen, Christian; Roddy, Edward; Prinjha, Suman; Ziebland, Sue; Hider, Samantha
Abstract Background Gout is more common in men, and is often perceived by both patients and health practitioners to be a disorder of men, but its prevalence in women is increasing. Little is known about women's experience of gout and the impact it has on their lives. It is important for practitioners to be aware of these areas, given the increasing numbers of women with gout they are likely to see in the future. This study aimed to explore women's experiences of gout. Methods A qualitative research design was used. Semi-structured interviews were conducted with 43 people, of whom 14 were women. Interviews were video and/or tape recorded and transcribed verbatim. Data from the interviews was first grouped into broad categories, followed by a more detailed thematic analysis and interpretation. Results Participants' ages ranged from 32 to 82. Nine participants were retired and five were in fulltime work. Four themes emerged: (1) experience of onset, help seeking and diagnosis (2) understanding and finding information about gout, (3) impact on identity, and (4) impact on roles and relationships. Conclusions The diagnostic process for women with gout can be uncertain due to lack of awareness of gout in women (by health care professionals and women themselves). Women do not have a good understanding of the condition and find it difficult to find information that feels relevant to them. Gout has a major impact on women's identity and on their roles and relationships. These findings are of importance to health care professionals dealing with women with potential gout and those with an existing diagnosis.